2022
DOI: 10.3390/signals3030031
|View full text |Cite
|
Sign up to set email alerts
|

Urban Plants Classification Using Deep-Learning Methodology: A Case Study on a New Dataset

Abstract: Plant classification requires the eye of an expert in botanics when the subtle differences in stem or petals differentiate between different species. Hence, an accurate automatic plant classification might be of great assistance to a person who studies agriculture, travels, or explores rare species. This paper focuses on a specific task of urban plants classification. The possible practical application of this work is a tool which assists people, growing plants at home, to recognize new species and to provide … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…The results showed that the framework could detect five distinct disease classes with an average accuracy of 73.3%. In [14], the authors investigated the effectiveness of pre-trained classification models and transfer learning to improve results in the urban planter dataset, consisting of fifteen urban plant species.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…The results showed that the framework could detect five distinct disease classes with an average accuracy of 73.3%. In [14], the authors investigated the effectiveness of pre-trained classification models and transfer learning to improve results in the urban planter dataset, consisting of fifteen urban plant species.…”
Section: Related Workmentioning
confidence: 99%
“…It reduces our burden for performing complex tasks such as pattern recognition, classification, disease detection, and language analysis [6,7,11,12]. Recently, it has also been rigorously used in the Agri-domain, especially for the detection of plant disease; crop prediction; plant categorization; pest range; and pesticide impact assessment [1,6,13,14].…”
Section: Introductionmentioning
confidence: 99%
“…Litvak et al (2022) [ 15 ] recently contributed to the field of plant species classification by introducing the Urban Planter dataset. This dataset consists of 1500 images categorized into 15 plant species categories, and the authors evaluated various pre-trained CNN models to classify the plant species.…”
Section: Related Workmentioning
confidence: 99%
“…It plays a significant role in various fields, including botany, agriculture, and ecological research. Existing works in plant leaf classification have utilized handcrafted features combined with traditional machine learning [ 1 , 2 , 3 , 4 , 5 , 6 , 7 ] or deep learning models [ 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 ] for feature extraction and classification. However, these approaches have certain limitations that reduce their effectiveness in accurately classifying plant leaves.…”
Section: Introductionmentioning
confidence: 99%